The Physicochemical Properties And Effect Of Storage Period On Powder Properties Of Instant ‘Masak Lodeh’ - Hasbullah, Nur Ili (Pusat Pengajian Teknologi Industri, 2021)
Convenience foods demand on supply of world’s population has been overwhelming over the past few decades. Therefore, development and invention of formulations of new products has increased drastically. The objectives of this study are to develop and analyze the physicochemical properties and effect of storage on powder properties of instant ‘Masak Lodeh’. Instant ‘Masak Lodeh’ was cooked and subjected to freeze drying before grounded to be powdered ‘Masak Lodeh’. Color, moisture, bulk density, flowability and insolubility index were analyzed on different storage period in this study. Furthermore, proximate composition, mineral determination and total plate count were carried out through this study.